Captain Underpants and the perilous plot of Professor Poopypants : the fourth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2000)
When Professor Pippy P. Poopypants comes to Jerome Horwitz Elementary School to teach science, and he goes off the deep end because students make fun of his name, only Captain Underpants can save the school from the professor's perilous plot.
Keywords: Escuelas -- Literatura juvenil